2022
DOI: 10.3390/nu15010081
|View full text |Cite
|
Sign up to set email alerts
|

Ergogenic Aids to Improve Physical Performance in Female Athletes: A Systematic Review with Meta-Analysis

Abstract: Most intervention studies investigating the effects of ergogenic aids (EAs) on sports performance have been carried out in the male population. Thus, the aim of this systematic review and meta-analysis was to summarize the effects in the existing literature of EAs used by female athletes on performance. A literature research was conducted, and a descriptive analysis of the articles included in the systematic review was carried out. Meta-analyses could be performed on 32 of the included articles, evaluating per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Another study focused on ergogenic supplements' effects on the performance of cycling athletes; they had a positive effect on the speed and endurance of the cyclists [54]. Similarly, López-Torres et al [55] discovered that the consumption of ergogenic supplements aided in the performance of female athletes and enhanced their efficacy to reach specific physical needs and goals. In addition, Gacek [56] investigated the determinants of nutritional choices of Polish handball players; it was found that self-efficacy and the consumption of vegetables are positively correlated, thus indicating their belief in achieving specific goals.…”
Section: H3mentioning
confidence: 99%
“…Another study focused on ergogenic supplements' effects on the performance of cycling athletes; they had a positive effect on the speed and endurance of the cyclists [54]. Similarly, López-Torres et al [55] discovered that the consumption of ergogenic supplements aided in the performance of female athletes and enhanced their efficacy to reach specific physical needs and goals. In addition, Gacek [56] investigated the determinants of nutritional choices of Polish handball players; it was found that self-efficacy and the consumption of vegetables are positively correlated, thus indicating their belief in achieving specific goals.…”
Section: H3mentioning
confidence: 99%
“…In recent years, professional sports teams and amateur enthusiasts have widely embraced natural plant extracts and phytochemicals to enhance their athletic performance, speed up post-exercise recovery, and maintain their overall physical health ( Striegel et al, 2005 ; Kim et al, 2011 ; Darvishi et al, 2013 ; Knapik et al, 2016 ). Polyphenols represent a crucial category of natural botanical extracts, and there is mounting evidence to suggest their significant potential in enhancing athletic performance and aiding recovery ( Bai et al, 2022 ; Liu et al, 2022 ; López-Torres et al, 2022 ; Sánchez Díaz et al, 2022 ; Roberts et al, 2023 ; Zare et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the quest for optimal performance, athletes and coaches have a range of potential pre-conditioning and nutritional strategies at their disposal, many of which can be employed to facilitate performance on the day of competition 5 , 6 . In the context of the latter, nutritional ergogenic aids, such as caffeine (CAF), have the potential to acutely facilitate performance in a variety of settings and hence they are widely consumed by athletes 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In the quest for optimal performance, athletes and coaches have a range of potential pre-conditioning and nutritional strategies at their disposal, many of which can be employed to facilitate performance on the day of competition 5 , 6 . In the context of the latter, nutritional ergogenic aids, such as caffeine (CAF), have the potential to acutely facilitate performance in a variety of settings and hence they are widely consumed by athletes 6 , 7 . Performance improvements following ingestion of CAF may be manifested through a variety of potential mechanisms, including binding to adenosine receptor sites, concomitant release of neurotransmitters, altered RPE and pain perception, enhanced muscle contractile properties, and improved intramuscular metabolic environment 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation